ANALYSIS OF CREATIVE THINKING SKILLS BASED ON COGNITIVE LEVEL - Fitriyani, Fitriyani; Gunawan, Gunawan; Purwanto, Joko; Wijaya Kusuma, Jaka (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to describe students' creative thinking skills in solving mathematical problems reviewed from the cognitive level. The research was carried out at Putra Harapan Junior High School Purwokerto. The research method used is qualitative descriptive. Based on previous cognitive tests, students are grouped into cognitive levels, namely very good, good, good enough, not good, and not good. The instruments used in this study consist of written tests and interview guidelines. Data analysis techniques include data reduction, data presentation, and conclusion. The study results show that students in the very good and good category can meet the aspects of fluency and flexibility. Students can understand and work on the questions appropriately and confidently. Students of the excellent category can find many ideas and completion methods that can be applied correctly. The students who are quite good and those who are poor have difficulty finding solutions and using them in problems. Students in the not-good category cannot correctly fulfil the aspects of creative thinking, namely fluency and flexibility, and they have difficulties understanding the initial problem